Real-Time Controller Based on FPGA and DSP for Solar Ground Layer Adaptive Optics Prototype System at 1-m NVST - Lin Kong; Lei Zhu; Lanqiang Zhang; Hua Bao; Changhui Rao (IEEE Photonics Journal, 2017)
Solar ground layer adaptive optics (GLAO), containing a large field of view (FOV) wavefront sensor (WFS) and one deformable mirror (DM), can be used to reduce and stabilize the seeing effectively over a wide FOV. As the brain of the GLAO system, the real-time controller (RTC) computes the commands to drive the DM according to the average wavefront errors measured by the multi-direction correlating Shack–Hartmann WFS, which is a time-consuming process. A customized RTC based on a high-speed field programming gate array and a multi-core digital signal processor was developed for the solar GLAO prototype system at the 1-m New Vacuum Solar Telescope. Several parallel acceleration techniques are used to reduce the computation time of the RTC. Compared with the previous RTCs, our RTC architecture has nearly no timing jitter. In this paper, the design of the RTC for our solar GLAO prototype will be introduced. The test results of the RTC are also presented. Moreover, the on-sky Sun observational results of the solar GLAO prototype are shown.